Reflexions on the Role of the “Ordre Public” in the EU Regulations on Civil Procedure: Razprave / Discussions - Mansi , Francesco (LeXonomica, 2011)
It is generally acknowledged that the system introduced by the 1968 Brussels Convention on the jurisdiction and the enforcement of judgements in civil and commercial matters (1968 Brussels Convention) and the EC Regulation 44/2001 on jurisdiction and the recognition and enforcement of judgements in civil and commercial matters1 (Regulation 44/2001) has been working well over the past forty years.2 In spite of that, in the last years the discussion arose about the public policy exception in the recognition and enforcement of foreign decisions. Particularly, it has been suggested that this provision should not be any longer necessary and that it should consequently be cancelled from all regulations, in order to make the recognition and enforcement faster and easier.